Visibility and Effectiveness of PJOK Learning in Junior High Schools in Buleleng District - I Wayan Restu Adi Wiguna; I Gede Suwiwa; I Ketut Yoda (Universitas Pendidikan Ganesha, 2024)
Sports and health physical education involves physical activity for students which aims to improve fitness, improve students' motor skills, healthy living behavior, and foster sportsmanship. The aim of this research was to determine the visibility and effectiveness of PJOK learning in junior high schools (SMP) throughout Buleleng Regency. This type of research is descriptive - quantitative with data collection techniques namely 1) Survey, 2) Observation, 3) Documentation study, and 4) Interview. The sample used in this research was 46 schools from a population of 72 schools. The results of this research show the first two results in terms of learning visibility, namely that the personality competency score is 7.05 in the